Empire, the British Museum, and the Making of the Biblical Scholar in the Nineteenth Century Archival Criticism - Cuéllar, Gregory Lee (Cham Springer International Publishing AG, 2019)
Intro -- Acknowledgments -- Contents -- List of Figures -- Chapter 1: Introduction: Historicizing the Master Archive -- The Politics of the Master Archive -- The Indexes of Subjectivity for the Archive -- Critiquing the Master Archive as a Biblical Scholar -- Trespassing on the Archive as Method -- Bibliography -- Chapter 2: Mastering Biblical History in the British Museum -- Seeing Is Believing -- Multivalent Inscriptions of Power -- Scientific Exploration in the Public Domain -- Historical Geography and the Bible -- Layard's Nimrud in the British Museum -- The Antiquarian Gaze of the British Museum -- The British Museum's Machinery of Affiliations -- Conclusion -- Bibliography -- Chapter 3: Books and Bodies in the British Museum Reading Room -- Equating Skull Size with Superior Intellect -- Panoptic Knowledge and Encyclopedic Learning -- The Reading Room as a Panoptic Machine for Knowledge -- Gendered Space in the Reading Room -- Reproducing Empire in the Reading Room -- The Printed Bible Collection and Clergy Readers -- Conclusion -- Bibliography -- Chapter 4: The Biblical Critic as Collector -- Biblical Critic as Collector of Manuscripts -- Westcott's Private Collecting Habits -- Collecting Natural Objects with School Boys -- Feasting Eyes at the British Museum -- The Confines of Textual Collecting -- Textual Collecting at a State Museum -- Shaping the Textual Critic Through Museum Access -- Conclusion -- Bibliography -- Chapter 5: Biblical Scholar as Imperial State Agent -- Customizing Archaeological Science for the Department of Antiquities -- Samuel Birch and the Department of Oriental Antiquities -- Aligning Museum Artifacts with Biblical History -- Touring Birch's Department as an Orientalist -- Racial Seeing of Museum Artifacts -- Samuel Rolles Driver as Scholar Agent of the British Museum -- Linking Museum Artifacts to Biblical History.
Description based on publisher supplied metadata and other sources
Keywords: Bible-Theology; Electronic books